Seleucid royal cities as a model for Artaxata? Considerations on the urban planning of the Hellenistic Armenian capital - Held , Winfried (ARAMAZD: Armenian Journal of Near Eastern Studies, 2025)
In 187 BC, Artaxias I turned Armenia, previously ruled by the Seleucids, into an independent kingdom and founded a new capital, Artaxata. Buildings on a range of hills are known from this city; it is however unclear how far the city extended into the plain. It is also uncertain where the palace was located. Based on the assumption that Artaxata was modeled on the royal cities of the Seleucids, an attempt is made hereafter to reconstruct the outlines of the original urban planning of Artaxata. If the premise is correct, Artaxias would have planned a city of 600 ha or more from the outset, encompassing the entire area between the ancient course of the Metsamor, the Araxes and the chain of hills. Inside, it would have a regular street grid and insulae of identical size. The palace district would be located in the south at the mouth of the Metsamor and Araxes and would cover around a quarter of the city’s area.